2022
DOI: 10.1371/journal.pcbi.1009780
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation modelling of networks of heterogeneous care homes and the inter-facility spread of Covid-19 by sharing staff

Abstract: Although system dynamics [SD] and agent-based modelling [ABM] have individually served as effective tools to understand the Covid-19 dynamics, combining these methods in a hybrid simulation model can help address Covid-19 questions and study systems and settings that are difficult to study with a single approach. To examine the spread and outbreak of Covid-19 across multiple care homes via bank/agency staff and evaluate the effectiveness of interventions targeting this group, we develop an integrated hybrid si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Although modeling studies have demonstrated that agency nurses are a key risk for the spread of SARS-CoV-2 across long-term care homes, this risk can be mitigated with better training, routine testing, and the formation of workplace "bubbles" that limit the number of care homes where staff work. 20,21 In addition to limiting worker mobility, initiatives that reduce the chance of onward transmission within the households of RACS staff members should be considered as part of the public health response to COVID-19 outbreaks in the aged-care sector. Other strategies could include readily accessible supported accommodation programs, which provide hotel or other accommodation for front-line staff who are working during an outbreak, 22 as well as broad close-contact definitions for RACS staff, provided there were adequate staff replacements available.…”
Section: Discussionmentioning
confidence: 99%
“…Although modeling studies have demonstrated that agency nurses are a key risk for the spread of SARS-CoV-2 across long-term care homes, this risk can be mitigated with better training, routine testing, and the formation of workplace "bubbles" that limit the number of care homes where staff work. 20,21 In addition to limiting worker mobility, initiatives that reduce the chance of onward transmission within the households of RACS staff members should be considered as part of the public health response to COVID-19 outbreaks in the aged-care sector. Other strategies could include readily accessible supported accommodation programs, which provide hotel or other accommodation for front-line staff who are working during an outbreak, 22 as well as broad close-contact definitions for RACS staff, provided there were adequate staff replacements available.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the integrated hybrid SD-ABM model was to understand the impact that temporary bank/agency staff, who work across multiple care homes, have on the spread of COVID-19 in care homes and to evaluate the effectiveness of a range of intervention strategies (Nguyen, Megiddo, and Howick, 2022).…”
Section: Approachmentioning
confidence: 99%
“…A detailed discussion of categories of information flows follows. These categorizations emerged from a literature review of hybrid SD-ABM models across various domains and were based on reflection from the modeling process of our case study (Nguyen, Megiddo, and Howick 2022). For each category of information flow, we provide a description and one or two example models selected from the literature.…”
Section: Addressing a Limitation Of Existing Guidance For Combining S...mentioning
confidence: 99%
“…White and black boxes denote elements of an SD and ABM module, respectively. Green arrows denote the flows of information found in the literature, and red arrows denote the proposed flows based on reflection from the modeling process of our case study (Nguyen, Megiddo, and Howick 2022) (1) Stock levels affect agent-specific state variables or are used to generate a small crowd of agents; (2) Stock levels affect agent's behaviors; (3) Stock levels bound aggregate measures of agents; (4) Stock levels affect the network topology of agents; and (5), ( 6), (7), and (8): Agent-specific state variables, agents' behaviors, aggregated measures of agents, and the network topology of agents affect flows of an SD module respectively.…”
Section: Addressing a Limitation Of Existing Guidance For Combining S...mentioning
confidence: 99%